Liver biomarkers of silymarin milk thistle on paracetamol induced liver toxicity in adult albino rats (Rattus norvegicus) - Ngetich, Davis Kiprono; Korir, Scolastica (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Paracetamol is the most common analgesic that is readily available with or without prescription over the counter and its toxicity is due to misuse or overdose associated with liver damage. Silymarin milk thistle is an edible herb believed to have antioxidant, scavenging and regulation of glutathione contents within the cell. Aim of the study was to determine the effects of different doses of silymarin milk thistle on liver biomarkers of paracetamol induced liver toxicity among albino rats. Methods: Twenty-four adult albino rats were randomly grouped into four groups each group consisting of six animals. Paracetamol-only group given high dose paracetamol-750 mg/kbwt and control group received water and food only. The experimental group, were divided into three subgroups with all receiving high dose paracetamol for five days and thereafter given varying doses of silymarin milk thistle. SIL-G1 given 200 mg/kbwt of silymarin milk thistle, SIL-G2 given 400 mg/kbwt of silymarin milk thistle and SIL-G3 was given 600 mg/kbwt of silymarin milk thistle. All the animals were fed with standard rodent foods and water ad libitum. After completion of 24 hours of the last drug administration, they were humanely sacrificed, serum biochemical analysis of liver biomarkers (ALP, ALT and AST) was determined. Results: High dose of paracetamol induced liver toxicity. Upon administration of high dose of silymarin milk thistle, there was restoration of ALP, AST and ALP of all these biomarkers in relation to the control group. Conclusions: These findings showed that high dose (600 mg/kbwt) of silymarin milk thistle was found to have restorative effects and normalized liver biomarkers of ALP, AST and ALT.